Moral Values in the Film Not One Less《一个都不能少》 张艺谋对《一个都不能少》电影道德价值分析 - Fakhriawan Fathu Rahman; Tuty Wulandari Bin Ahmad; Syafri Badaruddin; M. Amir P.; Citra Andini (Hasanuddin University, 2023)
The objective of this research is to examine the form of moral values and to explain what are the moral values of the main character, namely Wei Minzhi in the film